Peningkatan Pemahaman tentang Relasi Positif dan Mencegah Toxic Relationship pada Kader Posyandu Remaja SMART Sampit, Kalimantan Tengah: Increasing Understanding of Positive Relationships and Preventing Toxic Relationships among SMART Youth Posyandu Sampit, Central Kalimantan - Maydana Izati; Riza Amalia; Siti Halimah; Dinda Andina (PengabdianMu: Jurnal Ilmiah Pengabdian kepada Masyarakat, 2023)
Based on the results of a preliminary survey conducted with SMART Posyandu cadres using a Google form questionnaire, it was found that 100% of respondents stated that they had experienced negative relationships with friends, and 83% stated that they had experienced toxic relationships in friendships, so based on these results it is necessary to carry out counseling about understanding positive relationships and prevent toxic relationships. This activity aims to increase understanding of positive relationships and prevent toxic relationships—implementation of activities carried out through three stages: preliminary survey, planning, and implementation. The activity begins with giving a pretest and ends with giving a posttest to find out the level of understanding about positive relationships and preventing toxic relationships. The results obtained after counseling showed an increase in understanding; out of 22 participants, 11 people experienced an increase, seven got a fixed score, and only four got a decreased score. After counseling is carried out, the next step is to assist in strengthening the understanding of SMART Posyandu cadres in establishing positive relationships and preventing toxic relationships in friendships.